2000
DOI: 10.1097/00005373-200005000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Incidence, Clinical Significance, and Prognostic Value of Circulating Cardiac Troponin I and T Elevation in Hemodynamically Stable Patients with Suspected Myocardial Contusion after Blunt Chest Trauma

Abstract: Although improved specificity of cTn-I and cTn-T compared with conventional markers, it should be emphasized that the main problem with cTn-I and cTn-T is low sensitivity as well as low predictive values in diagnosing myocardial contusion. cTn-I and cTn-T measurement is currently not an improved method in diagnosing blunt cardiac injury in hemodynamically stable patients. Moreover, there was no association of postmyocardial contusion cell injury and late outcome in these patients when cTn-I and cTn-T and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
10

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(86 citation statements)
references
References 33 publications
5
71
0
10
Order By: Relevance
“…Troponin T (TnT) and troponin I (TnI) are regarded as the featured indicators in slight cardiac injuries. [3,4] Changes in levels of tumor necrosis factor (TNF)-alpha might be determined due to myocyte damage secondary to cardiac spasm-traumatic cardiac injuries. [5] Ideal trauma grading systems should target the correct definition of all damage and the severity of each type of damage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Troponin T (TnT) and troponin I (TnI) are regarded as the featured indicators in slight cardiac injuries. [3,4] Changes in levels of tumor necrosis factor (TNF)-alpha might be determined due to myocyte damage secondary to cardiac spasm-traumatic cardiac injuries. [5] Ideal trauma grading systems should target the correct definition of all damage and the severity of each type of damage.…”
Section: Resultsmentioning
confidence: 99%
“…18 Sayı -No. 4 293 On the other hand, a statistically significant relationship between ECG changes and ECHO findings was reported in a study dealing with a series of 81 patients by Weiss et al [16] Abnormal ECHO findings (ventricular function disorders and pleural effusion) were detected in eight of 15 exitus cases.…”
mentioning
confidence: 91%
“…Diagnosing cardiac contusion remains difficult, because most diagnostic tests are nonspecific and no gold standard is currently available [1,11,12]. Therefore, a high index of suspicion and clear clinical judgment are equally necessary in the diagnosis and management of patients with BCI [2,5,11].…”
Section: Discussionmentioning
confidence: 99%
“…An ECG can be used as a screening tool for cardiac injury when the patient is presented at the emergency department and BCI is suspected [1][2][3][4][5][6]. ECG abnormalities are frequently demonstrated in patients following blunt chest trauma and can be nonspecific [1,6,9,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac troponins are most specifi c amongst conventional markers as they differ from the skeletal isoform by a unique aminoterminal sequence of 31 amino acids never expressed by skeletal muscle [43]. Cardiac troponin-I has shown maximum sensitivity (23-100%) and specifi city (85-97%) in detecting clinically signifi cant BCI [34][35][36][37][38][39][40][41][42][43][44][45][46]. Velmahos et al [47] concluded that, 100% negative predictive value was reached on combining ECG with troponin-I at 8 hours.…”
Section: Cardiac Markersmentioning
confidence: 99%